Contribution of Social Support to Parenting Self-Efficacy from Mothers with Children with Autism - Febrianti, Vinesia; Hildayani, Rini (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Autism Spectrum Disorder (ASD) is one of the developmental disorders commonly found in children. Parenting a child with autism is challenging. Parents, especially mothers, play a crucial role in raising children with autism, but mothers often experience difficulties and high levels of stress. This underscores the need for parenting self-efficacy to support their caregiving. Parenting self-efficacy is influenced by several factors, one of which is social support. This study aims to examine the influence of social support on the parenting self-efficacy of mothers of children with autism. Additionally, it seeks to identify the significant sources of social support that affect the parenting self-efficacy of mothers with children with autism. The research was conducted using a quantitative approach involving 79 mothers in Indonesia. Data were collected using questionnaires containing the Self-Efficacy for Parenting Task Index (SEPTI) and The Multidimensional Scale of Perceived Social Support (MSPSS) distributed online. The collected data were analyzed using descriptive statistics and multiple linear regression. The analysis revealed that social support influences the parenting self-efficacy of mothers of children with autism. Furthermore, it was found that support from partners is a significant source of social support affecting the parenting self-efficacy of mothers. This research emphasizes the importance of parental cooperation in raising children with autism. Autism spectrum disorder (ASD) merupakan salah satu gangguan perkembangan yang banyak ditemukan pada anak-anak. Pengasuhan bagi anak penyandang autisme merupakan sesuatu yang menantang. Orang tua, khususnya ibu, memiliki peranan penting dalam pengasuhan anak penyandang autisme, tetapi ibu seringkali mengalami kesulitan dan tingkat stres yang tinggi. Hal ini mendorong kebutuhan akan adanya parenting-self efficacy untuk mendukung pengasuhan mereka. Parenting self-efficacy dipengaruhi oleh beberapa faktor, salah satunya adalah dukungan sosial. Melalui penelitian ini, ingin diketahui pengaruh dukungan sosial terhadap parenting self-efficacy ibu yang memiliki anak penyandang autisme. Kemudian, ingin diketahui sumber dukungan sosial yang berperan secara signifikan terhadap parenting self-efficacy ibu dari anak penyandang autisme. Penelitian dilakukan dengan pendekatan kuantitatif terhadap 79 ibu di Indonesia. Data diperoleh dengan menggunakan kuesioner yang memuat instrumen Self-Efficacy for Parenting Task Index (SEPTI) dan The Multidimensional Scale of Perceived Social Support (MSPSS) yang disebarkan secara daring. Data yang terkumpul dianalisis menggunakan statistik deskriptif dan regresi linear berganda. Berdasarkan hasil analisis, diketahui bahwa dukungan sosial berperan terhadap parenting self-efficacy ibu dari anak penyandang autisme. Selain itu, ditemukan bahwa dukungan dari pasangan merupakan sumber dukungan sosial yang dapat berperan terhadap parenting self-efficacy ibu. Hasil penelitian ini menekankan pentingnya kerjasama orang tua dalam pengasuhan anak penyandang autisme.